Genetically Modified Labeling Policies: Moving Forward or Backward? - Borges, Bárbara Juliana Pinheiro; Arantes, Olivia Márcia Nagy; Fernandes, Antonio Alberto Ribeiro; Broach, James R.; Fernandes, Patricia Machado Bueno (Frontiers in Bioengineering and Biotechnology, 2018)
One of the priorities to address food security is to increase the access of farmers to biotechnology, through the application of scientific advances, such as genetically modified organisms and food (GMF). However, the spread of (mis)information about their safety strengthens the clamor for mandatory GMF labeling. This paper provides an overview of food labeling policies, considering the principles suggested by the Codex Alimentarius Commission, and analyzes the consequences for the world food security of the Brazilian labeling policies compared to developed countries. We discuss the discriminatory application of GMF mandatory labeling in the absence of any scientific evidence as it has the potential of causing social harm and jeopardizes research, production, and distribution of food and consumers' right to information.